Paradigma Islam Universal dalam Fatwa Etika Dakwah Digital di Indonesia - Istiani, Nurul (Tadbir: Jurnal Manajemen Dakwah FDIK IAIN Padangsidimpuan, 2023)
The presence of qualitative studies through this normative-philosophical approach has the maximum to identify the dimensions of universal Islamic values in the fatwa of the Indonesian Ulema Council of East Java Province Number. 06 of 2022 concerning Da'wah Ethics in the Digital Era. The existence of Islamic universalism is the basis for perspective in the main discussion of this study, and the analysis of this study data through reduction, presentation, and verification. The results of this study show the content of universal Islamic values in legal provisions related to da'wah ethics in the didital space in the fatwa of the Indonesian Ulema Council of East Java Province, including the value of tafahum in the prohibition of profocative da'wah content. Then, the value of tasamuh in the recommendation of da'wah content that respects plurality. Furthermore, the value of takaful in the recommendation of da'wah content that maintains public conduciveness. The theoretical implications of this study assert that Islamic universalism can be internalized by religious social fatwas in Indonesia.